(untitled) (Global Journal of Management and Business Research, 2020)
The gender division of labour still remains today a disadvantage for women to achieve their economic autonomy. Responsibility for care giving tasks and the values associated with what is feminine and masculine build distinct places for men and women in society which, despite all the advances and achievements of recent decades, seem immutable. The aim of this work is to draw a picture of women’s economic autonomy in Brazil and Minas Gera is from the relationship established between paid and unpaid work, based on the National Continuous Household Sample Surveys (PNADc) of the Brazilian Institute of Geography and Statistics (IBGE). The results show that the disadvantages faced by Brazilian women in relation to men persist in most inequality metrics and show that the possibilities of career progression and unrestricted access to the world of work remain associated with cultural values, discrimination and strategies of subordination.